O fenômeno da hibridação cultural: análise semiótica da indumentária ressignificada da Quadrilha Eita Junino em Boa Vista – Roraima - Cunha, Frank Dennis Martins (Universidade Federal de Roraima, 2022)
In this paper trace considerations about hybridity and semiotics as corpus using the photographs and costumes of Square Dancer Eita Junino the years 2006 to 2012. The research is based on the theoretical framework settled in Canclini (2003), Stuart Hall (2006 ), Peirce (2012), Merrell (2012) and others have found that culture as something moving and construction. Finally, the semiotic approach will bring about the many ways that signs provide within a semiosic universe, and this is under constant construction and movement.